Politeness in Cross-Cultural Interactions in Sofia Coppola's 'Lost in Translation' - Iskandar, Iskandar; Mappaita, Suci Pole; Mohamad, Andi Riswan (Seminar Nasional LP2M UNM, 2025)
Abstract. This article explores the complexities of politeness in cross-cultural interactions as depicted in Sofia Coppola's 2003 film, Lost in Translation. Set in Tokyo, the film provides a rich narrative for analyzing the pragmatic challenges faced by its two American protagonists, Bob Harris and Charlotte, as they navigate an unfamiliar linguistic and cultural landscape. Drawing upon Brown and Levinson's politeness theory and contemporary models of intercultural pragmatics, this study examines how face-threatening acts (FTAs), politeness strategies, and communicative misunderstandings are portrayed. The analysis focuses on key scenes that highlight the divergence in communication styles between American and Japanese cultures, particularly concerning directness, indirectness, the use of silence, and non-verbal cues. The discussion reveals how the film masterfully illustrates the limitations of universal politeness maxims and emphasizes the role of cultural context in shaping perceptions of what is considered polite or impolite. Through a detailed cinematic analysis, the article argues that Lost in Translation serves as a poignant case study on how linguistic barriers and cultural dissonance can lead to feelings of alienation and a deeper search for connection. The findings contribute to the fields of intercultural communication, pragmatics, and film studies, offering insights into the nuanced dynamics of maintaining face in unfamiliar cultural settings.Key Words: Politeness Theory, Cross-Cultural Interaction, Intercultural Pragmatics, Lost in Translation, Sofia Coppola, Face-Threatening Acts, Japanese Culture, Film Analysis